The Phenomenon of Endorsement on Instagram Social Media In Consumer Society (Descriptive Study of FEBI UINSU Students) - Andra Bebi Masyitha; Devi Yana Sari; Hamzah Arif Sirot; Inayatul Widad Nasution; Moch Rizfani Rifky; Rina Syafitri (International Journal of Cultural and Social Science, 2021)
Endorsement is an act of support (support) or agreement on something. Endorse is currently booming on social media, especially on Instagram. Online shopping finally uses endorse services to promote goods that will be consumed by the public. One of the problems faced today is the endorsement phenomenon that is carried out on Instagram social media, which makes the consumer community continue to shop online, in the midst of teenagers who are the target of marketing by the market. Through this research, the researcher wants to know how the endorse phenomenon on social media Instagram in the consumer society of FEBI UINSU students. This research is a qualitative descriptive research that makes individuals as research subjects. Research informants were determined by a purposive procedure. Data were collected using three methods, namely interviews and observation. In conducting interviews, the informants were FEBI UINSU students who had the criteria of informants in this study, totaling 15 informants. Data interpretation is carried out in stages starting from data collection, data reduction until conclusions and research recommendations are obtained. From the results of research that has been done that FEBI UINSU students often do online shopping because of the influence of endorsements on Instagram social media. Endrse's influence, which is currently booming, creates a desire to continuously consume. This is also driven by family economic factors that support consumption activities. This situation also finally makes the teenager shop no longer because of need but because of the value of the sign attached to the item. Therefore, FEBI UINSU students show consumptive behavior.